Scale development for school administrators' corporate reputation building studies - Akilli, Ceyda (Emerald Group Publishing Ltd, 2023)
PurposeThe aim of this research is to develop a scale that determines the views of teachers on the efforts of educational administrators to build corporate reputation within the scope of modern education paradigms.Design/methodology/approachThe research is based on a scale development method whose validity and reliability analyzes have been completed.FindingsAs a result of the research, a 1-dimensional and 15-item scale was obtained, which aims to evaluate the corporate reputation building efforts of school administrators from the perspective of teachers. When the literature is examined, there are many scales on corporate reputation; however, the literature determined that there is no scale that aims to determine the opinions of teachers about the reputation building efforts of education administrators.Originality/valueEducational administrators engage in efforts to build corporate reputation through stakeholder analysis, needs analysis, strategic plan development, organizational design and change management (Lawler et al., 2006). Specializing in this field is very important for training managers by taking training on human resources in order to carry out effective work in the process of corporate reputation formation, and the human resources of the institution are the groups that will best evaluate the reputation building efforts of the managers (Lockwood, 2007).
Keywords: School administrators; Corporate reputation; Scale development; Teachers